2009
DOI: 10.4269/ajtmh.2009.09-0131
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of the Dengue Virus Type 4 Vaccine Candidate rDEN4Δ30-4995 in Healthy Adult Volunteers

Abstract: Abstract. rDEN4D30-4995 is a live attenuated dengue virus type 4 (DENV4) vaccine candidate specifically designed as a further attenuated derivative of the rDEN4D30 parent virus. In a previous study, 5 of 20 vaccinees who received 10 5 plaque-forming units (PFU) of rDEN4D30 developed a transient elevation of the serum alanine aminotransferase (ALT) level and an asymptomatic maculopapular rash developed in 10 of 20. In the current study, 28 healthy adult volunteers were randomized to receive 10 5 PFU of rDEN4D30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…The assay was identical to that used in the Laboratory of Infectious Disease (National Institute of Allergy and Infectious Diseases [NIAID], National Institutes of Health, Bethesda, MD). 14 Exchange of 20 serum samples from a DENV vaccine trial 15 determined that our results for serotype 4 were comparable to those obtained at the National Institutes of Health. This is an important consideration because variability has been shown in the DENV neutralization assay.…”
Section: Methodssupporting
confidence: 67%
“…The assay was identical to that used in the Laboratory of Infectious Disease (National Institute of Allergy and Infectious Diseases [NIAID], National Institutes of Health, Bethesda, MD). 14 Exchange of 20 serum samples from a DENV vaccine trial 15 determined that our results for serotype 4 were comparable to those obtained at the National Institutes of Health. This is an important consideration because variability has been shown in the DENV neutralization assay.…”
Section: Methodssupporting
confidence: 67%
“…Significant progress in the development of dengue vaccine candidates has been achieved lately 135,136 . An Acambis/Sanofi Pasteur yellow fever-dengue chimeric vaccine is in advanced Phase II testing in children in Thailand and others are in Phase 1 or advanced preclinical evaluation.…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…The rDEN4D30-200,201 and rDEN4D30-4995 candidates were more attenuated than the rDEN4D30 parent in monkeys and SCID mice reconstituted with human liver cells (HuH 7) [20,119] but still elicited neutralizing antibodies. Clinical trials were performed with both vaccines (Table 13) [112,113]. These studies showed that the vaccines were more attenuated than parental rDEN4D30, produced no viremia, little or no hepatotoxicity (0% of subjects for rDEN4D30-200,201; 10% for rDEN4D30-4995), and lower neutralizing antibody levels, and a lower incidence of neutropenia and generalized rash.…”
Section: Chimeric Dengue/dengue and Deletion Mutant Vaccine Candidatementioning
confidence: 99%
“…The -4995 candidate was associated with a localized rash around the injection site in a high proportion of subjects. Sera from vaccinees in different trials who received rDEN4D30-4995, rDEN4D30-200,201 and rDEN4D30 in different trials were compared in a single neutralization test [112]. The rDEN4D30-200,201 candidate had a GMT only twofold lower than rDEN4D30.…”
Section: Chimeric Dengue/dengue and Deletion Mutant Vaccine Candidatementioning
confidence: 99%